2021
DOI: 10.1055/a-1422-2631
|View full text |Cite
|
Sign up to set email alerts
|

Long-term endoscopic follow-up after closure of a post-bariatric surgery fistula with a cardiac septal defect occluder

Abstract: Long-term endoscopic follow-up after closure of a post-bariatric surgery fistula with a cardiac septal defect occluder E-VideosVideo 1 Long-term follow-up of successful gastrocutaneous fistula closure using a cardiac septal defect occluder.▶ Fig. 1 Endoscopic images showing: a the well-positioned cardiac septal defect occluder, with closure of the gastrocutaneous fistula at 1-year follow-up; b no evidence of leakage or a fistulous tract, despite apparent migration of the cardiac septal defect occluder, at 3-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Different from several studies, 5,8,14,28 we reported the use of adjunctive endoscopic approaches in a substantial part of our population. This finding is related to our experience in treating these challenging conditions, as described in Methods 27,29–34 . It is important to state that there is no gold standard method to treat TGID.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Different from several studies, 5,8,14,28 we reported the use of adjunctive endoscopic approaches in a substantial part of our population. This finding is related to our experience in treating these challenging conditions, as described in Methods 27,29–34 . It is important to state that there is no gold standard method to treat TGID.…”
Section: Discussionmentioning
confidence: 64%
“…This finding is related to our experience in treating these challenging conditions, as described in Methods. 27,[29][30][31][32][33][34] It is important to state that there is no gold standard method to treat TGID. An individualized approach considering personal/local experience is required.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of the use of CSDO for the treatment of GI fistulas is not novel, albeit formally it is considered an off-label indication. Its use in the setting of post-bariatric fistula treatment is still very limited to a small number of case reports [ 5 , 10 , 11 , 12 ]. To the best of the authors’ knowledge, no reports on the use of the Occlutech® devices for this purpose are available comparable to former studies with the Amplatzer TM Occluders.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Early results suggest this technique is particularly useful for poor surgical candidates with chronic GI fistulas that have had failure of closure attempted with standard endoscopic methods [ 8 ]. In these cases, the persistent inflammation, fibrosis, and epithelialization of the tract is often not liable to the application of clips, sutures, sealants, and conventional ablative techniques, leading to failed closure attempts in up to 20% of cases [ 12 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%